Implied terms in English contract law - Austen-Baker, Richard (Elgar commercial law and practice, 2017)
This book is the leading account of contract law in England and Wales in relation to implied terms. Implied terms are not only frequently of great importance in litigation, but can assist business parties in planning contracts effectively by allowing them to identify issues over which they do not need to negotiate because they would be content with the terms the law would imply. Distinct commercial advantages of this approach can include savings of management time in negotiating and avoiding trade-off costs demanded by counterparties in exchange for agreeing an express term. This Second Edition has been fully revised and updated to cover recent developments in the law. Key features include: - full analytical treatment of featured cases and evaluation of recent case law in relation to use of implied terms - analysis of the major changes to statutory implied terms brought by the Consumer Rights Act 2015 - useful synoptic tables showing how these changes map across the different categories within the CRA and between the CRA and pre-existing legislation - extended discussion of statutory implied terms in services contracts - detailed examination of the decisions of the Privy Council in A-G of Belize v. Belize Telecom and of the UK Supreme Court in BNP Paribas v. Marks & Spencer. This book will be an invaluable resource for all legal practitioners, both in practice and in-house, involved in contract drafting and contract negotiations. It also acts as a helpful reference for scholars and students in the field of contract law.